Modified Bi‐Rads Scoring of Breast Imaging Findings Improves Clinical Judgment. Issue 6 (28th September 2015) - Silberman, Howard; Sheth, Pulin A.; Parisky, Yuri R.; Hovanessian‐Larsen, Linda J.; Sheth, Sindu; Tripathy, Debasish
Abstract: In contrast with the reporting requirements currently mandated under the Federal Mammography Quality Standards Act (MQSA), we propose a modification of the Breast Imaging Reporting and Data System (Bi‐Rads) in which a concluding assessment category is assigned, not to the examination as a whole, but to every potentially malignant abnormality observed. This modification improves communication between the radiologist and the attending clinician, thereby facilitating clinical judgment leading to appropriate management. In patients with breast cancer eligible for breast conserving therapy, application of this modification brings to attention the necessity for such patients to undergo pretreatment biopsies of all secondary, synchronous ipsilateral lesions scored Bi‐Rads 3‐5. All contralateral secondary lesions scored Bi‐Rads 3‐5 also require pretreatment biopsies. The application of this modification of the MSQA demonstrates the necessity to alter current recommendations ("short‐interval follow‐up") for secondary, synchronous Bi‐Rads 3 ("probably benign") image‐detected abnormalities prior to treatment of the index malignancy.